2020
DOI: 10.1101/2020.07.28.224634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TOR coordinates with transcriptional and chromatin machinery to regulate thermotolerance and thermomemory

Abstract: Global warming exhibits profound effects on plant fitness and productivity. To withstand stress, plants sacrifice their growth and activate protective stress responses for ensuring survival. However, the switch between growth and stress is largely elusive. In the past decade, emerging role of Target of Rapamycin (TOR) has been studied linking energy and stress signaling. Here, we have identified an important role of Glc-TOR signaling in plant adaptation to heat stress (HS). We show that Glc-TOR signaling regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The glc-TOR-E2Fa signaling pathway has also been implicated in thermotolerance and thermomemory [ 157 , 158 ]. Glc-activated TOR phosphorylates E2Fa which binds to the promoter of HLP1 (Hikeshi Like Protein 1), an ortholog of human Hikeshi.…”
Section: Tor Signaling In Photosynthetic Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glc-TOR-E2Fa signaling pathway has also been implicated in thermotolerance and thermomemory [ 157 , 158 ]. Glc-activated TOR phosphorylates E2Fa which binds to the promoter of HLP1 (Hikeshi Like Protein 1), an ortholog of human Hikeshi.…”
Section: Tor Signaling In Photosynthetic Organismsmentioning
confidence: 99%
“…Glc-TOR signaling promotes long-term acquired thermotolerance by modifying the chromatin landscape at thermomemory-related loci by promoting H3K4 trimethylation (H3K4me3). Together, these studies show that glc-TOR signaling is important for control of thermotolerance and thermomemory, thus protecting plants from heat stress [ 157 , 158 ]. Recently it has been shown that autophagy negatively regulates thermomemory by selectively targeting heat shock proteins (HSPs) for degradation, and remains highly induced during thermorecovery [ 159 , 160 ].…”
Section: Tor Signaling In Photosynthetic Organismsmentioning
confidence: 99%
“…Glc-TOR signaling promotes long-term acquired thermotolerance by modifying the chromatin landscape at thermomemory-related loci by promoting H3K4 trimethylation (H3K4me3). Together, these studies show that glc-TOR signaling is important for control of thermotolerance and thermomemory, thus protecting plants from heat stress [157,158]. Recently it has been shown that autophagy negatively regulates thermomemory by selectively targeting heat shock proteins (HSPs) for degradation and remains highly induced during thermorecovery [159,160].…”
Section: Energy/glucose and Lightmentioning
confidence: 95%